Effect of proximal optimization technique on coronary bifurcation stent failure: Insights from the multicenter randomized PROPOT trial. Issue 4 (16th February 2022) - Murasato, Yoshinobu; Watanabe, Yusuke; Yamawaki, Masahiro; Kinoshita, Yoshihisa; Okubo, Munenori; Yumoto, Kazuhiko; Masuda, Naoki; Otake, Hiromasa; Aoki, Jiro; Nakazawa, Gaku; Numasawa, Yohei; Ito, Tatsuya; et al.
Abstract: Objective: We investigated the effect of proximal optimization technique (POT) on coronary bifurcation stent failure (BSF) in cross‐over stenting by comparing with the kissing balloon technique (KBT) in a multicenter randomized PROPOT trial. Background: POT is recommended due to increased certainty for optimal stent expansion and side branch (SB) wiring. Methods: We randomized 120 patients treated with crossover stenting into the POT group, which was followed by SB dilation (SBD), and the KBT group. Finally, 52 and 57 patients were analyzed by optical coherence tomography before SBD and at the final procedure, respectively. Composite BSF was defined as a maximal malapposition distance of >400 μm, or malapposed and SB‐jailed strut rates of >5.95% and >21.4%, respectively. Results: Composite BSF before SBD in the POT and KBT groups was observed in 29% and 26% of patients, respectively. In the POT group, differences in stent volumetric index between the proximal and distal bifurcation (odds ratio [OR] 60.35, 95% confidential interval [CI] 0.13–0.93, p  = 0.036) and between the proximal bifurcation and bifurcation core (OR: 3.68, 95% CI: 1.01–13.40, p  = 0.048) were identified as independent risk factors. Composite BSF at final in 27% and 32%, and unplanned additional procedures in 38% and 25% were observed, respectively. Composite BSF before SBD was a risk factor for the former (OR: 6.33, 95% CI: 1.10–36.50, p  = 0.039) and the latter (OR: 6.43, 95% CI: 1.25–33.10, p  = 0.026) in the POT group. Conclusion: POT did not result in a favorable trend in BSF. Insufficient expansion of the bifurcation core after POT was associated with BSF.